Restoring realism: themes and variations. Issue 5 (3rd May 2020) - Affifi, Ramsey
Abstract: In the critical tradition, environmental education discourse interrogates how knowledge constructs experience. But environmental education also emphasises perceiving, understanding and responding to "more-than-human" beings and processes. These two motivations are in tension. One problem is that the epistemological orientation driving the critique of knowledge seems to render access to something more-than-human a priori impossible. But environmental education squanders its promise and its dream if only ever permitted to talk about the natural world with scarequotes. Our field urgently needs to develop a realism robust against epistemologies that construct impassable barriers between humans and the rest of creation. I propose that this starts with radically reconceiving the nature and relationship between similarity and difference, interpreted in this article as the dynamic between theme and variations. Reworking Windelband's distinction between idiographic and nomothetic research, I suggest that the relationship between theme and variation manifests a fundamental ontological pattern that pervades all things. "Theme and variation" proposes a unifying metaphysical duality in which the more-than-human reveals itself in how things suggest, conform to, modulate, and violate generalisation. Acknowledging and investigating this is part of restoring to other beings and processes their metaphysical, aesthetic, and ethical status, from the skies to the psyche.